2001
DOI: 10.1042/cs1000199
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular regulation during head-up tilt in healthy 20–30-year-old and 70–75-year-old men

Abstract: This study compared the heart rate, finger arterial pressure (AP) and electromyographic (EMG) activity of selected anti-gravity muscles during the initial and prolonged phases of orthostatic stress in healthy young and older men. Beat-by-beat recordings of heart rate, finger systolic pressure, diastolic pressure and mean AP were made during supine rest and 5 min of 90 degrees head-up tilt (HUT) in 18 young (23+/-1 years) and 15 older (73+/-1 years) men. The EMG activity of the soleus, tibialis anterior and vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…However, similar BP responses during HUT were reported in healthy subjects by Gabbett et al [29], who conducted a 90°HUT test on young males, and observed that a BP overshoot in an early stage of HUT to about 10 mmHg above the supine value. It has been widely accepted that considerable individual variations exist in orthostatic tolerance [25,26,30,31].…”
Section: Responses To Hutmentioning
confidence: 60%
“…However, similar BP responses during HUT were reported in healthy subjects by Gabbett et al [29], who conducted a 90°HUT test on young males, and observed that a BP overshoot in an early stage of HUT to about 10 mmHg above the supine value. It has been widely accepted that considerable individual variations exist in orthostatic tolerance [25,26,30,31].…”
Section: Responses To Hutmentioning
confidence: 60%
“…The acute cardiac frequency increase in response to the rapid change into the orthostatic posture, in general occurring within the fi rst seconds after standing upright, although present in all individuals, decreases in magnitude with age, and can be delayed 118 . This decrease in the variability of the cardiac frequency observed in elderly patients, when compared to young individuals in the orthostatic versus the supine posture, has been attributed to a decrease in the recruitment of baroreceptor activity when the upright position is adopted 17,117,118 .…”
Section: Understanding Of Cardiovascular Adaptation To Orthostatism -mentioning
confidence: 99%
“…However, the analysis of cardiac frequency in healthy individuals in the sitting posture has shown that cardiac frequency decreases with age in both sexes 116,117 . The studies utilizing the IT to assess the cardiovascular adaptation to orthostatic stress also reported a signifi cantly lower cardiac frequency in elderly individuals 17,117,118 . We know that the resting cardiac frequency is modulated, in part, by the equilibrium between the sympathetic and the parasympathetic tonus, with a predominance of the latter.…”
Section: Understanding Of Cardiovascular Adaptation To Orthostatism -mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not the case at the cardiac frequency scale. Indeed, the effect of pleural pressure on the heart is quite well elucidated [22]. Nonetheless, to our knowledge, the reciprocal effect of heart on pleural pressure is not clear: the beating heart can be considered as a volume and/or pressure change generator inside the rib cage as evidenced by its effect on lung volume [23].…”
Section: Renal Modulementioning
confidence: 99%